Eating behaviour among undergraduate students. Comparing nutrition students with other courses - Poinhos, Rui (2015)
Our main aim was to compare eating behaviour between Portuguese undergraduate nutrition students and students attending other courses. Several eating behaviour dimensions were compared between 154 nutrition students and 263 students from other areas. Emotional and external eating were assessed by the Dutch Eating Behavior Questionnaire, dietary restraint was measured using the flexible and rigid control of eating behaviour subscales, binge eating was measured using the Binge Eating Scale, and eating selfefficacy using the General Eating Self-Efficacy Scale. Higher levels of flexible and rigid control were found in nutrition students from both sexes when compared to students from other courses. Female nutrition students also presented higher binge eating levels than their colleagues from other courses. To our knowledge no other work has previously assessed all eating behaviour dimensions considered in the current study among nutrition students. Besides the results by themselves, the data obtained from this study provide several clues to further studies to be developed regarding the still rarely approached issue of eating behaviour among nutrition students.